Mutu Pendidikan Kelompok Bermain Nur Masithah Sampang Di Tinjau Dari Prinsip ISO 9001:2015 - Farida Farida; Chasan Ma'ruf (Thawalib: Jurnal Kependidikan Islam, 2023)
The aim of this research is to find out and describe the picture of the quality of the Nur Masitha Sampang Playgroup in terms of the seven principles of ISO 9001:2015. Qualitative research methods with a case study approach. Data collection techniques: interviews with 1 principal, 2 teachers, 2 students, and 2 parents; observation and documentation. Data processing: reduction, data presentation, and conclusion. Data validity with technique and source triangulation. The results of the research show: (1) leadership principles: democratic leadership. (2) the principle of customer focus: learning and playing, books, educational game tools, and parenting. (3) the principle of engagement of people: principals, teachers, and parents. (4) process approach principles: learning schedules, weekly and daily program implementation plans, SOPs for arrival and return of students. (5) the principle of improvement: innovation of indoor and outdoor learning processes. (6) principles of evidence-based decision making: improving learning through meetings at the end and beginning of the semester. (7) the principle of relation management: cooperation with the Sampang Himpaudi group and parents.